The Development of the 2020 Multifunction DA Plyometric Wicket Tool for Central Java PPLDP Athletes (Journal of Physical Education and Sports, 2022)
Today, the development of various sports in Indonesia is quite fast. Sport cannot be separated from the training process. Sports require physical and technical training in order to create qualified athletes. However, the availability of facilities and infrastructure, especially training aids, is still left behind, especially for plyometric training. The tools used are still not practical to use. Based on the above, it is necessary to develop products for assistive devices that can facilitate both athletes and coaches to practice and maximize their abilities. The purpose of this research is to produce a multifunction of DA 2020 plyometric goal that can be used to train athletes in various sports at PPLDP Central Java. This research is a development research, as for product development procedures, namely, conducting a needs analysis that will be developed and obtained from the results of a literature review, observation and interviews, developing an initial product draft, expert validation, improvement of the initial product draft, small-scale trial, first product revision, product revisions based on the results of expert evaluation and small-scale trials,field trials, final product revisions based on field trials, the final result is the 2020 Multifunction DA Plyometric Goal media for plyometric jumping exercises for athletes at PPLDP Central Java. The instruments used in this study were questionnaires, observations, interviews and documentation. Through this research, evaluation data of athlete trainers and product appraisal experts were obtained with an average percentage of 89% and meets the “Very Good” criteria. While the small- scale trial data obtained a percentage of 84% and field trials of 87%, thus meeting the "Very Good" criteria. From these data, it can be concluded that the 2020 Multifunction DA Plyometric Goals media is effective to be used as a medium for athletes plyometric jump training at PPLD Central Java.